The effect of interleukin-10 and transforming growth factor β-1 on HLA-DR expression in colonic epithelial cells - M. J. Zimmerman; G. R. Radford-Smith; D. P. Jewell (Hindawi Limited, 1998)
The aim of this study was to assess whether interleukin-10 (IL-10) and/or transforming growth factor β-1 (TGF β1) downregulate HLA-DR expression using the HT29 cell line as a model of colonic epithelial cells. HLA-DR expression was induced in HT29 cells with γ-interferon. The effects of IL-10 alone, TGF β1 alone, and IL-10 and TGF β1 in combination were studied. HLA-DR expression was assessed using flow cytometric analysis. γ-Interferon induced HLA-DR expression in a dose-dependent fashion. In the absence of γ-interferon, neither IL-10 nor TGF β1 induced HLA-DR expression. In isolation, neither IL10 nor TGF β1 downregulated HLA-DR expression. When IL-10 and TGF β1 were added in combination, small (6-30%) statistically significant reductions in HLA-DR expression were seen. The biological significance is unclear.